An Exegetical-Hermeneutical Study of Romans 2:24: Christian Witness in Light of Orwell’s Animal Farm - Jabes Pasaribu; Selvyen Sophia; Rosnita Temba Kagu (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This article interprets Romans 2:24 within Paul’s argument in Romans 2:17–29 and in light of its prophetic background in Isaiah 52:5 and Ezekiel 36:20–23. Using a qualitative exegetical-hermeneutical approach, the study argues that Romans 2:24 should be read not merely as a moral rebuke against religious inconsistency but as a theological indictment of failed public representation: the people of God may become the very occasion through which God’s name is dishonored among outsiders. The exegetical analysis is then placed in a disciplined hermeneutical dialogue with George Orwell’s Animal Farm, treated not as a primary source of meaning but as a secondary allegorical lens that clarifies how a community can maintain normative claims while betraying them in practice. The study shows that the contradiction between confession and conduct, sustained at times by narrative self-justification, undermines the credibility of Christian witness in the public sphere. Accordingly, Romans 2:24 carries enduring significance for Biblical Studies and for contemporary ecclesial life: it locates credible public witness not in communicative strategy but in the covenantal coherence of a community whose embodied life either commends or dishonors the name it bears.